A lost family-planning regime in eighteenth-century Ceylon. (2nd January 2016) - Drixler, Fabian F.; Kok, Jan
Abstract : Based on Dutch colonial registers (thombos), this paper reconstructs fertility for two districts in Ceylon, 1756–68. It overcomes challenges in data quality by establishing the outer bounds of plausible estimates in a series of scenarios. Among these, total fertility rates (TFRs) averaged 5.5 in one district, but only 2.7 in the other. These figures exclude the victims of infanticide, a custom noted in European travelogues between about 1660 and 1820. Sex ratios among children differed depending on the number of older siblings, and overall, 27 per cent of girls are missing in one district and 57 per cent in the other. There was little significant variation either in the TFR or the sex ratio by socio-economic status, suggesting that poverty was not a key factor in motivating infanticides. Instead, we argue that at least parts of Ceylon had a forward-looking culture of family planning in the eighteenth century, which was lost in subsequent decades.